Possible Health Effects of a Wax Ester Rich Marine Oil - Schots, Pauke Carlijn; Pedersen, Alice Marie; Eilertsen, Karl-Erik; Olsen, Ragnar Ludvig; Larsen, Terje Steinar (Frontiers in Pharmacology, 2020)
The consumption of seafood and the use of fish oil for the production of nutraceuticals and fish feed haves increased over the past decades due the high content of long-chain polyunsaturated omega-3 fatty acids. This increase has put pressure on sustainable the sustainability of fisheries. One way to overcome the limited supply of fish oil is to harvest lower in the marine food web. Calanus finmarchicus, feeding on phytoplankton, is a small copepod constituting a considerable biomass in the North Atlantic and is a novel source of a marine oil rich in theseomega-3 fatty acids. The oil is, however, different from other commercial marine oils in terms of chemistry and, possiblye also, bioactivity since it contains wax esters. Wax esters are fatty acids that are esterified with alcohols. The fatty acids of the oil are mainly esterified to long-chain fatty alcohols, forming a lipid class known as wax esters. In addition to the long-chain polyunsaturated omega-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), the oil is also rich in stearidonic acid (SDA),and long-chain monounsaturated fatty acids, and the long-chain fatty alcohols eicosenol and docosenol. Recent animal studies have indicated anti-inflammatory and anti-obesogenic actions of this copepod oil beyond that provided by EPA and DHA. This review will discuss potential mechanisms behind these beneficial effects of the oil , focusing on the impact of the various components of the oiland its components. The health effects of EPA and DHA are well recognized, whereas long-chain monounsaturated fatty acids and long-chain fatty alcohols have to a large degree been overlooked in relation to human health. Recently, however the fatty alcohols have received interest as potential targets for improved health via conversion to their corresponding fatty acids. Together, the different lipid components of the oil from C. finmarchicus may have potential as nutraceuticals for reducing obesity and obesity-related metabolic disorders.